Analisis Investasi Terhadap Pertumbuhan Ekonomi - Kesia Septina Putri Tarigan; Jessica Simanungkalit; Tasya Oren Sagala; Yesi Veronica (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the relationship between investment and economic growth in North Sumatra Province during the period of 2005–2023. The main focus is on how investment, both Domestic Investment (PMDN) and Foreign Direct Investment (FDI), influences the Gross Regional Domestic Product (GRDP) as the primary indicator of economic growth. Using a descriptive qualitative method based on secondary data, the study finds that FDI tends to have a more significant impact on economic growth compared to domestic investment. Moreover, investment also plays a role in increasing employment opportunities and interacts with other variables such as inflation and government spending. The findings show that the impact of investment on economic growth can vary depending on macroeconomic conditions and other structural factors. Therefore, optimizing investment requires support from inclusive and sustainable development policies.